2010
DOI: 10.1007/s00264-010-1119-0
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of double-eccentric hemi shoulder arthroplasty in different aetiologies: midterm results

Abstract: This prospective study aimed to analyse the effect of a newly developed double-eccentric adjustable stemmed prosthesis on reconstruction of the osseous anatomy, range of motion, strength and pain relief. A total of 91 consecutive hemiprostheses were evaluated preoperatively and three, six, 12, 24 and 48 months postoperatively (mean±SD 46.2 ± 10.9 months) by the American Shoulder and Elbow Surgeons (ASES) and Constant scores as well as radiological assessment. Clinical evaluations showed an increase in Constant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
7
1
Order By: Relevance
“…We found an overall decrease in the rate of instability (1% [35 of 3,360 shoulders 9,20,21, 32,40,41,43,52,55,62,68,71,72,74,[76][77][78]83,87,103,106,108,[112][113][114][115][116]118,119,[121][122][123][124] ] in the current study compared with 4.9% [124 of 2,540 shoulders] in the earlier study 1 ). Component malposition (nonanatomic humeral and glenoid retroversion) and rotator cuff deficiency may lead to adverse kinematics of the glenohumeral joint, subsequent instability, edge loading of the glenoid component, and premature loosening 1,133 .…”
Section: Anatomic Tsacontrasting
confidence: 43%
See 2 more Smart Citations
“…We found an overall decrease in the rate of instability (1% [35 of 3,360 shoulders 9,20,21, 32,40,41,43,52,55,62,68,71,72,74,[76][77][78]83,87,103,106,108,[112][113][114][115][116]118,119,[121][122][123][124] ] in the current study compared with 4.9% [124 of 2,540 shoulders] in the earlier study 1 ). Component malposition (nonanatomic humeral and glenoid retroversion) and rotator cuff deficiency may lead to adverse kinematics of the glenohumeral joint, subsequent instability, edge loading of the glenoid component, and premature loosening 1,133 .…”
Section: Anatomic Tsacontrasting
confidence: 43%
“…Treatment options depend on the etiology of humeral component loosening and may require glenoid component removal, stem revision for aseptic loosening 157 , or single-stage versus 2-stage revision for infection158,159 .InfectionInfection after shoulder arthroplasty is a devastating event with negative health-related and fiscally associated implications. This analysis indicates an overall prevalence of 187,103,106,108,[112][113][114][115][116]118,119,[121][122][123][124] . With respect to RSA, some have ascribed increased rates of infection to hematoma formation and the so-called dead space associated with the lack of a rotator cuff127,158 , whereas others have attributed advanced patient age and prior shoulder surgery as risk factors127,150 .…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…19,32,33 The current authors' early results are slightly better compared with other results reported with stemmed implants. [34][35][36][37][38] The authors tried to minimize selection bias in this study by only including patients with an intact cuff (less than 1-cm rotator cuff tear) and glenohumeral osteoarthritis. Measurement bias was minimized by having assessors who were not involved with the original surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no evidence of that being the case (Table 1). We were able to verify in another study the accuracy of anatomical restoration with the prosthesis model used in this investigation [7]. The study showed that rotation centre restoration can be achieved with significantly more precision than with older, nonadjustable prostheses (Neer II, among others).…”
Section: Study Limitationsmentioning
confidence: 93%